Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Manajemen Laba Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sektor Industrials Yang Terdaftar Di BEI Tahun 2020-2024 - Winna Rahma Julita; Elfiswandi Elfiswandi; Putri Intan Permata Sari (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of profitability and firm size on earnings management with capital structure as an intervening variable in manufacturing companies in the industrials sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. This research employs secondary data obtained through documentation studies of companies’ financial statements accessed from the official IDX website (www.idx.co.id). The population of this study consists of 65 manufacturing companies in the industrials sector. Using a purposive sampling method, 17 companies were selected as the research sample. The data analysis methods include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing, and path analysis.The results indicate that profitability and firm size have an effect on capital structure. Partially, profitability and firm size do not have a direct effect on earnings management, whereas capital structure has a significant effect on earnings management. However, the path analysis results show that profitability and firm size affect earnings management through capital structure as an intervening variable. Thus, capital structure is proven to mediate the relationship between profitability and earnings management as well as the relationship between firm size and earnings management. These findings indicate that corporate financing decisions play an important role in encouraging earnings management practices, particularly in manufacturing companies in the industrials sector. This study is expected to provide empirical contributions to the development of financial management theory and serve as a consideration for company management, investors, and regulators in improving the quality of financial reporting.